Longitudinal stability analysis of a suborbital re-entry demonstrator for a deployable capsule. (January 2015) - Iacovazzo, Michele; Carandente, Valerio; Savino, Raffaele; Zuppardi, Gennaro
Abstract: In the field of atmospheric re-entry technology several research and industrial projects are based on the design of deployable, umbrella-like Thermal Protection Systems (TPSs) and aero-brakes. These systems are made of flexible, high temperature resistant fabrics, folded at launch and deployed in space for de-orbit and re-entry operations. This technology is very promising for low cost research and industrial applications, but requires to be validated by experimental flight tests. The University of Naples "Federico II" is currently working on the development of different down-scaled technological demonstrators for this kind of capsule to be launched by different classes of sounding rockets. In the present work an aerodynamic longitudinal stability analysis for a possible, suborbital re-entry demonstrator, has been performed in continuum and rarefied regimes. The longitudinal stability behavior of the capsule, along the entire re-entry path, has been investigated in the whole range of angle of attack and, in particular, around the nominal and the reverse equilibrium re-entry attitudes (i.e. around 0° and 180°, respectively) to implement a proper re-entry strategy able not to compromise the effectiveness of the flying system. Highlights: System concept for a suborbital demonstrator for a deployable re-entry capsule. Aerodynamic analysis during atmospheric re-entry. Longitudinal stability assessment in transitional and continuum flow regimes. Comparison between CFD and DSMC calculations in transitional regime.